2012
DOI: 10.3342/ceo.2012.5.4.240
|View full text |Cite
|
Sign up to set email alerts
|

A "Boxer Glove" Contoured Laryngeal Amyloidosis

Abstract: Laryngeal amyloidosis is uncommon and poorly understood, with limited long-term studies. Although primary localized laryngeal amyloidosis is extremely rare, it frequently involves the ventricles and the false and true vocal cords. We present a 58-year-old woman with localized laryngeal amyloidosis who presented no symptoms. On indirect laryngoscopic examination, the mass involved both arytenoids only, and had a likeness to a "boxer glove." She was treated surgically by microlaryngoscopy under general anesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Vocal fold injection for treating glottal insufficiency has gained popularity because of its noninvasiveness, its convenience, and the availability of variety injection materials 1,3,23-27. However, previously used graft materials were known to result in complications such as foreign body reactions or the formation of granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…Vocal fold injection for treating glottal insufficiency has gained popularity because of its noninvasiveness, its convenience, and the availability of variety injection materials 1,3,23-27. However, previously used graft materials were known to result in complications such as foreign body reactions or the formation of granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoidosis, metastatic tumors, polyps, malignant neoplasms, and salivary gland tumors are other possible differential diagnoses. 4 , 6 …”
Section: Discussionmentioning
confidence: 99%
“…Studies with long follow-up with amyloidosis of the larynx and trachea have reported that none of the patients developed systemic amyloidosis, B-cell lymphoma, or multiple myeloma. [5][6][7] Nevertheless, systemic workup is considered obligatory in every patient. Our patients had no lymphadenopathy, tender bones, and splenomegaly, which are suggesting the possibility of systemic amyloidosis.…”
mentioning
confidence: 99%